Persepsi Dan Sikap Bahasa Mahasiswa Terhadap Pembelajaran Bahasa Indonesia - Nursyaidah Nursyaidah; Fitri Rayani Siregar (Institut Agama Islam Negeri Padangsidimpuan, 2019)
The background of the research problem is students assume that Indonesian language courses are subjects that are considered easy and do not need to be studied on the grounds that they are able to speak Indonesian verbally, Indonesian has been used in everyday life both in formal and non-formal environments. This reason makes students assume that learning Indonesian does not need to be learned and is not included in the use of international languages as the language of communication between countries. If this continues, it can indicate the students' thinking that Indonesian is not important to learn and understand, thirdly, students assume that Indonesian language courses are only for meeting SKS and not for the importance of learning Indonesian language. If this statement is true then this subject is not yet based on its desire to know Indonesian language learning. The purpose of this study was to determine students' perceptions and attitudes towards first semester Indonesian language learning at IAIN Padangsidimpuan. This research method uses descriptive qualitative approach with this research data collection instrument in the form of questionnaires, observation and interview processing techniques and data analysis of this research is data editing, data reduction and drawing conclusions namely compiling data editions into systematic sentences. The result showed that the students think that bahasa Indonesia is easy to study, on the other hand they still unable to use it whether in daily communication or even in written expression. Their attitude to bahasa Indonesia is still low, it means that they are not care about bahasa Indonesia lesson because they think that it is not important for them, it is shown by inability of the students in writing scientific article